Rasio Fraksi Debu-Liat Sebagai Indikator Perkembangan dan Kesuburan Tanah - Muhammad Nuriman; Rini Hazriani; Tri Tiana Ahmadi Putri (Jurnal Solum, 2022)
Soil horizon development is a determinant of soil type and characteristics. The morphology reflects the stages of soil formation by observing the genetic horizon. The genetic horizon is a soil layer distinguished by symbols (O, A, E, B, C, and R). Soil formation can also be obtained from the silt-clay fraction as part of the soil texture observation. The silt-clay ratio can reflect the soil morphology and genesis. This study aimed to determine the silt-clay ratio as an indicator of soil development and fertility. This study was conducted in 2020 in Manismata Sub-District West Kalimantan Province with soil parent material derived from sedimentary rocks with the topography of 0-3%, 3-8%, and 8-15%. The observations were carried out on five soil profiles in terms of morphology, texture, organic matter, nitrogen, CEC, and Ca. Based on the results, entisol (regosol) had A-C genetic horizon and silt-clay ratio >2.73. Meanwhile, inceptisol (kambisol) had an A-B-C genetic horizon and a silt-clay ratio of 1.44 – 2.24. The silt-clay ratio in entisol had a significant influence on organic matter, CEC, and Ca of 75.79%, 86.98%, and 85.14%, respectively. Silt-clay ratio in inceptisol had a significant influence on organic matter, CEC, and Nitrogen. 3-8% inceptisol had a negative relationship of 67.25%, 52.33% and 84.59%, respectively. Meanwhile, 8-15% of Kambisol had a positive relationship with R2 of 69.08%, 54.49%, and 66.61%, respectively. The difference in the relationship (negative, positive) on inceptisol was due to 3-8% inceptisols having lithologic discontinuities. Thus, it can be concluded that the silt-clay ratio can be an indicator of soil development and fertility.Key words : Fertility, Morphogenesis, Silt/Clay, Soil Weathering